Transportation and Centering Ability of Neoniti and ProTaper Instruments; A CBCT Assessment - Madani, Zahrasadat; Soleymani, Ali; Bagheri, Tasnim; Moudi, Ehsan; Bizhani, Ali; Rakhshan, Vahid (Iranian Endodontic Journal, 2017)
Introduction: Transportation is an important iatrogenic endodontic error which might cause failure. This study evaluated the canal transportation caused by Neoniti and ProTaper instruments, using cone-beam computed tomography (CBCT) cross sections. Methods and Materials: This in vitro experimental study was performed on 40 mesiobuccal roots of maxillary first molars. The teeth were scanned with CBCT. They were randomly divided into 2 groups (n=20) that were prepared using either Neoniti or ProTaper files. An endodontist prepared the canal according to the manufacturer’s guidelines. Prepared canals were re-scanned. The pre-instrumentation and post-instrumentation CBCT volumes were sectioned at 1 to 9-mm distances from the apex. The extent of canal dentine removal in mesial and distal directions were measured in each cross-section. Canal transportation and instrument centering ability were estimated based on the extents of root wall removal and were compared in both groups. Results: The groups were rather similar in terms of transportation and centering ability (P>0.05). However, canal preparation on mesial and distal walls was statistically significantly less in the Neoniti group, at most cross-sections. Transportation of both groups was not significantly different (P>0.05). Centering ability of both instruments was not significantly different (P>0.05). Conclusion: Neoniti and ProTaper instruments might have proper centering ability and minimum transportations. Both instruments might cause similar extents of transportation and centering abilities. Keywords: Centering Ability; Nickel Titanium Instruments; Root Canal Treatment; Root Canal Preparation; Transportation